2004
DOI: 10.1676/0043-5643(2004)116[0083:dbafao]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Diving Behavior and Foraging Areas of the Neotropic Cormorant at a Marine Colony in Patagonia, Argentina

Abstract: The Neotropic Cormorant (Phalacrocorax brasilianus) is a widespread and abundant species distributed throughout the Neotropics. We report on diving behavior and foraging areas of Neotropic Cormorants in inshore marine waters of Patagonia, Argentina. Mean dive duration was 18.9 Ϯ 5.3 sec and differed significantly among birds. Maximum dive duration was 43 sec. Birds spent 58-79% of their time at sea underwater. Mean recovery time at the surface between successive dives was 6.7 Ϯ 1.5 sec, and was also significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 13 publications
0
14
1
4
Order By: Relevance
“…La dieta del yeco se compone principalmente de peces de tamaño pequeño que captura buceando en aguas poco profundas (Quintana et al 2004, González-Gajardo et al 2009). Mientras que la gaviota dominicana es una especie generalista, su dieta registra peces, invertebrados y una constante tendencia a la explotación de recursos de origen humano (Bertellotti & Yorio 1999, Silva et al 2000, Petracci et al 2004, Ludynia et al 2005.…”
Section: Resultados Y Discusiónunclassified
“…La dieta del yeco se compone principalmente de peces de tamaño pequeño que captura buceando en aguas poco profundas (Quintana et al 2004, González-Gajardo et al 2009). Mientras que la gaviota dominicana es una especie generalista, su dieta registra peces, invertebrados y una constante tendencia a la explotación de recursos de origen humano (Bertellotti & Yorio 1999, Silva et al 2000, Petracci et al 2004, Ludynia et al 2005.…”
Section: Resultados Y Discusiónunclassified
“…The weak relationship between surface rest and dive duration (slope 0.04) contrasts with most cormorants, which have slopes 0.3–1.4 (Croxall et al 1991, Wanless and Harris 1991, Hustler 1992, Frere et al 2002). Although some studies have found equally weak relationships among cormorants, with some regressions not significant (Quintana 1999, Quintana et al 2004), darters have a greater diving efficiency (5–6) than 18 species of cormorants (2.7±0.4) and other families of diving birds (average 0.2–4.3; Dewar 1924, Boyd and Croxall 1996, Walton et al 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Because observations on this species were incidental, no data on bout lengths were obtained. Comparative data on the relationships between dive parameters in other cormorants were obtained from the literature (Cooper 1986 and references therein; Wilson and Wilson 1988, Croxall et al 1991, Wanless and Harris 1991, Wanless et al 1993, 1995, Lea et al 1996, Grémillet et al 1999, Kato et al 1999, Quintana 1999, Frere et al 2002, Sapoznikow and Quintana 2003, Quintana et al 2004, Wilson and Quintana 2004).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the different diets of P. atriceps and P. brasilianus in Nahuel Huapi National Park might also be associated with different capabilities to forage on mid-water fish such as the Rainbow Trout and Brown Trout (Vigliano et al 2005). Whereas species belonging to the "Blue-eyed Shag Group", such as the Imperial Shag, are predominantly bottom feeders (Casaux and Barrera-Oro 2006), the Neotropical Cormorant is able to obtain its food throughout the water column (Quintana et al 2004). …”
Section: Patagonian Silverside (Odonthestes Hatchery)mentioning
confidence: 99%